Exploring the underlying mechanisms of exercise as therapy for multiple sclerosis: insights from preclinical studies - Du, Yunpeng; Dong, Shuhan; Zou, Wei (Frontiers in Cellular Neuroscience, 2024)
Multiple sclerosis (MS) is an immune-mediated disease of the central nervous system CNS characterized by demyelination, inflammation, and neurodegenerative changes, making it the most common nontraumatic disabling neurological disease in young adults. While current pharmacological treatments primarily target immunomodulation or immunosuppression, exercise is gaining increasing attention from the scientific community as an adjunctive therapy. This review explores the potential biological mechanisms of exercise in animal models of MS, focusing on its effects on neuroprotection and inflammation. The review examines how exercise inhibits pro-inflammatory microglial reactivity, stabilizes the blood-brain barrier, and enhances neurotrophic factor expression in animal studies. Future research directions are proposed by summarizing the evidence and limitations of existing animal models of MS, emphasizing the need to further validate these mechanisms in humans to better integrate exercise into the comprehensive management of MS. Additionally, investigating exercise-induced biomarkers for MS symptom reduction may provide a scientific basis for new therapeutic strategies.